1997
DOI: 10.1111/j.1365-2923.1997.tb02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Language background, English language proficiency and medical communication skills of medical students

Abstract: Associations between language background, English language proficiency and medical communication skills were investigated in a group of 149 third year undergraduate medical students studying at an Australian university. Written and aural English proficiency were assessed with the Screening Test for Adolescent Language (STAL). Medical communication skills and the fluency of spoken language were scored during an Observed Structured Clinical Interview (OSCI), rated by a standardized patient and a clinician. An as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
3
17
0
3
Order By: Relevance
“…The teaching skills of the workshop tutors, or the cultural or language backgrounds of the students, are other factors which might influence the variations in skill development by the students. Previous research 18 suggests that students with English speaking backgrounds are not necessarily more able to demonstrate empathy than are other students.…”
Section: Discussionmentioning
confidence: 95%
“…The teaching skills of the workshop tutors, or the cultural or language backgrounds of the students, are other factors which might influence the variations in skill development by the students. Previous research 18 suggests that students with English speaking backgrounds are not necessarily more able to demonstrate empathy than are other students.…”
Section: Discussionmentioning
confidence: 95%
“…In literature, it is reported that in undergraduate/graduate studies, students from English medium schools perform better than non English medium students. [13] Educational outcomes of urban students are also better than the rural students. [14] As students who are day scholars are mostly from Kolkata and nearby urban areas, they are more likely to have come from English medium schools, which explain their better performance compared to students with hostel aid.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Chur-Hansen et al, in 149 third-year medical students, it was observed that poor knowledge of English language was associated with poor performance in examination. [9] In a study done by Surya Raj Niraula et al, for 86 medical students of Nepal, it was observed that medium of schooling was associated with the high school marks, but it has no effect on marks obtained in any MBBS level. [10]…”
mentioning
confidence: 99%